Emotional Intelligence and Critical Thinking: Relevant Factors for Training Future Teachers in a Chilean Pedagogy Program - Maritza Palma-Luengo; Nelly Lagos-San Martin; Carlos Ossa-Cornejo (Journal of Intelligence, 2025)
Critical thinking has become one of the most notable cognitive skills in education in recent decades since it offers skills for improving knowledge, making decisions, and creativity, among others. While it is considered a mainly cognitive process, recent years have seen strong proposals regarding its relationship with motivational and emotional processes. A study is presented that analyzes the relationship between critical thinking and emotional intelligence, analyzing the relations and influences between these variables. Two instruments were applied to 658 Chilean pedagogy students with ages ranging from 19 to 47 years old. The results indicate a moderate level of critical thinking and a high level of emotional intelligence, along with a positive and significant but moderately low relationship between emotional intelligence and critical thinking. There are no gender differences, meaning that men and women developed these skills in a similar way, but differences were found between age groups. The study highlights the relevance of promoting both critical thinking and emotional intelligence in training future teachers and the need to generate new studies about how these skills are developed in teacher training.